Network meta-analysis of first-line systemic therapies for advanced hepatocellular carcinoma: Who is the winner?. (March 2023) - Celsa, C.; Cabibbo, G.; Rizzo, G.E.M.; Giuffrida, P.; Enea, M.; Di Maria, G.; Antonucci, M.; Giacchetto, C.M.; Rancatore, G.; Grassini, M.V.; Ciccia, R.; Grova, A.; et al.
Abstract : Introduction: Atezolizumab plus Bevacizumab represents the current standard of care for first-line treatment of advanced HCC. However, direct comparison with other combination treatments including immune-checkpoint inhibitors (ICI) plus tyrosine-kinase inhibitors (TKIs) or anti-CTLA4 are lacking. Aim: The aim of this network meta-analysis (NMA) is to indirectly compare the efficacy and the safety of first-line systemic treatments. Materials and Methods: Literature search of MEDLINE, EMBASE and SCOPUS databases was conducted up to October, 2022. Phase 3 randomized controlled trials (RCTs) testing TKIs, including Sorafenib and Lenvatinib, or ICIs reporting overall survival (OS) and progression-free survival (PFS) were included. Individual survival data were extracted from OS and PFS curves to calculate restricted mean survival time (RMST). A Bayesian NMA was performed to compare treatments in terms of efficacy (15- and 30-month OS, 6-month PFS) and safety, represented by grade≥3 (severe) adverse events (SAEs). The incremental safety-effectiveness ratio (ISER) as measure of net health benefit was calculated as the difference in probability of SAEs divided by difference in survival between the 2 most effective treatments. Results: Nine RCTs enrolling 6600 patients were included. Atezolizumab+bevacizumab showed the highest probability (88%) of being the best in 30-month OS. Pembrolizumab+lenvatinib showed the highest probability (94%) of being the best in terms of PFS. ICI monotherapies were the most safe combination. At a willingness-to-risk threshold of 10% of SAEs for month-year gained, atezolizumab+bevacizumab was favored in 76% of cases, while at a threshold of 30% of SAEs for month-year gained, pembrolizumab+lenvatinib was favored in 72% of cases. Conclusions: Atezolizumab plus Bevacizumab is the preferred option in unfit patients with high tumor burden, while Pembrolizumab plus Lenvatinib could be preferred for fit patients with less advanced vascular tumor spread